THE PLACE OF THE MARINA GENRE IN THE FINE ARTS - Hamidjonova Komila Davronjon qizi; P.hD Sharipjonov Muhiddin Shokirjon o’g’li (American Journals Publishing, 2024)
Marina genre is a genre that has received a lot of interest and attention in visual arts, and it captivates everyone with its complex appearance, contrast of colors, and depiction of various intense situations. To date, many artists have been creating in the Marina genre. The artists who work in the marine genre live in cities near the sea and oceans, and are engaged in depicting and promoting the landscape that inspires them. This article provides information about the role of visual art today and about visual art and its essence, types and genres. In fact, there are many types of art. There are also other types of art, such as fiction, music, visual arts, theater, cinema, choreography, architecture, applied decoration. Usually, the art that reflects the real existence in pictorial images, forms in a spatial dimension or plane (on the surface of paper) is called visual art.
Keywords: Fine art, painting, marina, landscape, genre, composition, perspective, etude, sea, beach, artist, I. Levitan, I. Shishkin, O. Tansikboev, I.K. Aivazovsky